A Perspective on the Use of Laboratory Market Experimentation in Auditing Research. - Boatsman, James R.; Grasso, Lawrence P. (The Accounting Review, 1992)
Provides an overview on the use of laboratory market experiment in auditing research. Concerns regarding the experiments and generality; Alternative approaches to characterizing equilibrium.